Toxicity studies using mammalian cells and impedance spectroscopy method - Xudong, Zhang; Fang, Li; Nordin, Anis Nurashikin; Tarbell, John; Voiculescu, Ioana (Elsevier B.V, 2015)
This research presents a study of cell-based Electric Cell-substrate Impedance Sensing (ECIS) sensors employed for testing toxicants in real-time. Mammalian cells are exposed to toxicants and information about cell viability are obtained from impedance measurements. The toxicants used are nicotine, phenol, ammonia and aldicarb. Two different adherent mammalian cells lines and cell culturewares were used to optimize the toxicity study. The cell lines used in this study were: bovine aortic endothelial cells (BAEC) and rat fat pad endothelial cells (RFPEC). The BAECs generated higher impedance values and formed cell monolayers at a faster rate compared to RFPECs. The two cell culturewares used in this study were simple open cell-culture wells and enclosed cell culturewares with microfluidic perfusion barriers. Experimental results indicated that the open wells are not suited for toxicity experiments. The turbulent flow created by pipetting media and toxicants in open cell culture wells disrupts the formation of the cell monolayer. When enclosed culture chambers were used, the flow of the cell culture medium and toxicant solutions were laminar on the cell monolayer. Both finite element simulations and experimental results showed that enclosed perfusion chamber have better performance due to the laminar flow of the solutions. The enclosed perfusion chamber also significantly shortens the response time of the cells when exposed to toxicants compared to the open cell culture wells. The experimental results demonstrated that ECIS biosensors seeded with BAECs inside enclosed cell culture chambers successfully assesses the effect of toxicants on mammalian cells in real-time.